Conflict resolution and creation of a security community in the Gulf Region - Niblock, Tim (Gulf Research Centre book series, 2018)
The bitter confrontation between Saudi Arabia and Iran is not only stoking conflicts in Syria, Iraq and Yemen, but now threatens the stability, security and well-being of the whole Gulf region. All the major global powers have significant interests in this area, and the pursuit of these interests adds further layers of division and conflict.